The Dyson Multiplying Effect - Diana Derval (NUST Business Review, 2019)
Talking about visionary entrepreneurs, Dyson revolutionized the quite boring home appliances category with a bag-less vacuum cleaner, a fan without blades, and more recently a 23.75 carat golden hairdryer. The group based in Malmesbury generated over 4 billion euros in sales last year, hitting a new high. Asia was driving 73% of this phenomenal 40% growth (1). But how did Dyson achieve this tour de force? What can other brands targeting the Asian or the luxury market learn from it? Dyson managed to dominate its markets with more expensive products, by targeting the right personas, making sure products are must-haves, demonstrating their benefits, learning from failure, and keeping a sharp vision.